Rasch Models of Aphasic Performance On Syntactic Comprehension Tests - Gutman, Roee (2010)
Responses of forty-two people with aphasia to eleven sentence types in enactment and sentence-picture matching tasks were characterized using Rasch models that varied in the inclusion of the factors of task, sentence type, and patient group. The best fitting models required the factors of task and patient group but not sentence type. The results provide evidence that aphasic syntactic comprehension is best accounted for by models that include different estimates of patient ability in different tasks and different difficulty of all sentences in different groups of patients, but that do not include different estimates of patient ability for different types of sentences.